Republic of Poland : Technical Assistance Report-Next Steps in Developing a Standard Chart of Accounts and Multi-year Budget. (IMF Staff Country Reports; Country Report ;, 2019)
This Technical Assistance report on the Republic of Poland provide details of an IMF mission to analyse next steps in developing a standard chart of accounts (SCoA) and multi-year budget. The Ministry of Finance (MoF) has started many preparatory activities for developing the SCoA. Extensive discussions and presentations during this mission afforded the mission the opportunity to convey information on the conceptual framework for the SCoA in more detail. Counterparts raised issues for clarification during initial meetings with the mission. Through a mini workshop, the mission tried to ensure that all counterparts fully understand the parameters of a multi-dimensional SCoA and the implication of decisions related to it. The main recommendations of this mission on the SCoA present various options available to address issues discussed. The mission recommended increasing the effectiveness of the accounting users' survey by ensuring that the SCoA survey respondents are made fully aware of the purpose of the survey and the implications of their responses.